2014
DOI: 10.1264/jsme2.me14086
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Variations in Sulfate-Reducing Communities Associated with a Terrestrial Hydrocarbon Seep

Abstract: Terrestrial hydrocarbon seeps are an important source of naturally emitted methane over geological time. The exact community compositions responsible for carbon cycling beneath these surface features remain obscure. As sulfate reduction represents an essential process for anoxic organic mineralization, this study collected muddy fluids from a high-temperature hydrocarbon seep in Taiwan and analyzed community structures of sulfate-supplemented sediment slurries incubated anoxically at elevated temperatures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Note in addition that this Firmicutes species was not restricted to these two juvenile chimneys and similar sequences were also reported under the accession numbers KF886161 (clone PHFST07_B16) and KF886087 (clone PHFST08_B19) in ST07 and ST08 sites (Supplementary Figure S1 ; Quéméneur et al, 2014 ) and under the accession number KJ159205 (clone PHF_15-B34_D22) in other chimneys of site ST09 ( Postec et al, 2015 ). As shown in Figure 7 and Supplementary Table S3 and with the sole exception of ST11d-17, the other sequences affiliated to the Firmicutes phylum in ST09 and ST11 related to sequences retrieved from other chimneys from PHF ST09 site ( Postec et al, 2015 ), in the serpentinization-driven subterrestrial alkaline aquifer of Cabeço de Vide aquifer in Portugal ( Tiago and Verissimo, 2013 ), in a deep H 2 -rich gold mine in the South Africa Precambrian craton ( Lin et al, 2006 ) and in a terrestrial hydrocarbon seep in Taiwan ( Cheng et al, 2014 ).…”
Section: Resultsmentioning
confidence: 98%
“…Note in addition that this Firmicutes species was not restricted to these two juvenile chimneys and similar sequences were also reported under the accession numbers KF886161 (clone PHFST07_B16) and KF886087 (clone PHFST08_B19) in ST07 and ST08 sites (Supplementary Figure S1 ; Quéméneur et al, 2014 ) and under the accession number KJ159205 (clone PHF_15-B34_D22) in other chimneys of site ST09 ( Postec et al, 2015 ). As shown in Figure 7 and Supplementary Table S3 and with the sole exception of ST11d-17, the other sequences affiliated to the Firmicutes phylum in ST09 and ST11 related to sequences retrieved from other chimneys from PHF ST09 site ( Postec et al, 2015 ), in the serpentinization-driven subterrestrial alkaline aquifer of Cabeço de Vide aquifer in Portugal ( Tiago and Verissimo, 2013 ), in a deep H 2 -rich gold mine in the South Africa Precambrian craton ( Lin et al, 2006 ) and in a terrestrial hydrocarbon seep in Taiwan ( Cheng et al, 2014 ).…”
Section: Resultsmentioning
confidence: 98%
“…The bottle was kept at room temperature in an anoxic chamber (Coy Laboratory Products, United States) for pre-incubation for 3 days to reduce any possible oxygen interference and stimulate the activity of anaerobic methane oxidizer. The basal salt solution was prepared in accordance with the general geochemical characteristics of the site following the recipe reported in Cheng et al (2014) with a chloride concentration adjusted to 500 mM. The reducing agent (Na 2 S × 9H 2 O) at a final concentration of 2.08 mM was added into the sterilized basal salt solution to decrease the redox potential and remove any trace amount of oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…In the current issue of Microbes and Environments, Cheng et al ( 4 ) reported that different types of sulfate-reducing prokaryotes that can be grown under specific temperatures ranges were detected in sulfate-amended enrichment cultures of muddy fluids taken from a Taiwanese terrestrial hydrocarbon seep, and that indigenous microbial communities might change based on the dynamic environmental fluctuations in volcanic mud ecosystems. Sulfate-reducing prokaryotes are frequently found in sulfate-supplied environment and are capable of growing on a variety of electron donors.…”
mentioning
confidence: 99%